The unsinkable Greta James : a novel - Smith, Jennifer E., 1980- (Ballantine Books, 2022)
"Right after the sudden death of her mother--her first and most devoted fan--and just before the launch of her high-stakes sophomore album, Greta James falls apart on stage. The footage quickly goes viral and she stops playing, her career suddenly in jeopardy--the kind of jeopardy her father, Conrad, has always predicted. Months later, Greta--still heartbroken and very much adrift--reluctantly agrees to accompany Conrad on the Alaskan cruise her parents had booked to celebrate their fortieth anniversary. It could be their last chance to heal old wounds in the wake of shared loss. But the trip will also prove to be a voyage of discovery for them both, and for Ben Wilder, a charming historian, onboard to lecture about The Call of the Wild, who is struggling with a major upheaval in his own life. As Greta works to build back her confidence and Ben confronts an uncertain future, they find themselves drawn to and relying on each other. It's here in this unlikeliest of places--at sea, far from the packed city venues where she usually plays and surrounded by the stunning scenery of Alaska--Greta will finally confront the choices she's made, the heartbreak she's suffered, and the family hurts that run deep. In the end, she'll have to decide what her path forward might look like--and how to find her voice again"--